THE EFFECT OF PROFITABILITY, LIQUIDITY, AND SOLVENCY ON GOING CONCERN AUDIT OPINION WITH COMPANY SIZE AS A MODERATING VARIABLE - Roidah, Lidya Sara; Subekti, Imam (Universitas Pembinaan Masyarakat Indonesia, 2024)
Research background: Going concern is a condition that assumes whether the company can continue to operate in the future. The issuance of this going concern audit opinion is a warning to companies and investors regarding business sustainability. Purpose of the article: This research aims to examine the factors of providing going concern audit opinions based on the theory of Audit Standards (SA) 570. The moderating variable in this research aims to test whether company size causes inconsistencies in previous research. Methods: The population includes Indonesian public companies in 2020-2022, from which 277 samples are selected though random sampling utilizing the Slovin formula. Findings & value added: The research results exhibit that liquidity and solvency ratios have a negative effect on going concern audit opinions as the greater the ability to pay debts, the smaller the possibility of receiving a going concern audit opinion. Profitability has no effect on going concern audit opinion because profitability does not always project a company's future financial potential. Company size weakens the effect of liquidity on going concern audit opinions for the larger the company size, the more difficult it is to prevent from receiving going concern audit opinions. Company size does not moderate the effect of profitability and solvency on going concern audit opinions because auditors do not consider company size as the main factor in assessing business continuity. JEL Classification: L2, M4, G33